Endolithic microbial composition in Helliwell Hills, a newly investigated Mars‐like area in Antarctica. (14th February 2021) - Coleine, Claudia; Biagioli, Federico; de Vera, Jean Pierre; Onofri, Silvano; Selbmann, Laura
Summary: The diversity and composition of Antarctic cryptoendolithic microbial communities in the Mars‐analogue site of Helliwell Hills (Northern Victoria Land, Continental Antarctica) are investigated, for the first time, applying both culture‐dependent and high‐throughput sequencing approaches. The study includes all the domains of the tree of life: Eukaryotes, Bacteria and Archaea to give a complete overview of biodiversity and community structure. Furthermore, to explore the geographic distribution of endoliths throughout the Victoria Land (Continental Antarctica), we compared the fungal and bacterial community composition and structure of endolithically colonized rocks, collected in >30 sites in 10 years of Italian Antarctic Expeditions. Compared with the fungi and other eukaryotes, the prokaryotic communities were richer in species, more diverse and highly heterogeneous. Despite the diverse community compositions, shared populations were found and were dominant in all sites. Local diversification was observed and included prokaryotes as members of Alphaproteobacteria and Crenarchaeota (Archaea), the last detected for the first time in these cryptoendolithic communities. Few eukaryotes, namely lichen‐forming fungal species as Lecidella grenii, were detected in Helliwell Hills only. These findings suggest that geographic distance and isolation in these remote areas may promote the establishment of peculiar locally diversified microorganisms.